APPLYING ISLAMIC COMMUNICATION ETHICS THROUGH SOCIAL MEDIA IN EARLY CHILDHOOD EDUCATION - Khairunnisa Ulfadhilah; Salsabila Dwi Nurkhafifah (QAULAN: Journal of Islamic Communication, 2025)
:  In today's digital era, social media is vital in shaping children's learning and communication, including within family-based early childhood education programs. This study explores how social media is applied in early childhood education programs to support children's education while adhering to Islamic communication ethics. Using a qualitative descriptive method, data were collected through interviews with parents, teachers, and administrators and observations of digital communication practices. The findings show that social media is an effective platform for sharing educational content, strengthening collaboration between parents and teachers, and introducing children to core Islamic values such as honesty, respect, and responsibility. However, the study highlights potential risks, including exposure to inappropriate content and children's lack of critical digital literacy. To address this, early childhood education programs emphasize parental involvement, ethical guidance, and structured media use. The study concludes that integrating Islamic communication ethics into digital parenting practices enhances learning and fosters moral development. These findings underscore the importance of a balanced, values-based approach to social media use in early childhood education settings. Keywords: Social Media; Islamic Communication Ethics; Early Childhood Education.